PENGARUH RESTRAIN PADA PASIEN PERILAKU KEKERASAN TERHADAP PENURUNAN PERILAKU KEKERASAN DI RUANG IGD RSJD ATMA HUSADA MAHAKAM SAMARINDA - Siti Nur Rahma; Edi Sukamto; Gajali Rahman (Poltekkes Kemenkes Kalimantan Timur, 2018)
ABSTRACTBackground: According to WHO data in 2012 the number of people with mental disorders worrying globally, about 450 million people suffering from mental disorders. People with mental disorders a third live in developing countries, as many as 8 out of 10 people with mental disorders that do not get treatment.Objective: To identify the effect of restrain on patient violent behavior toward decreasing violent behavior in room of ER Hospital Atma Husada Mahakam Samarinda.Design: The type of research used in this study is quasi experiment. Quasi experimental research is a study that tested an intervention in a group of subjects with or without a comparison group.Results: showing the characteristics of respondents mostly male sex numbered 14 people (70%) and women as many as 6 people (30%). And shows the characteristics of respondents by age less than 25 years as many as 6 people (30%), 26-40 years as many as 13 people (65%), and more ≥ 45 years as many as 1 person (5%).Test results Wilcoxon Test performed obtained value P = 0.001 (P <0.05)Conclusion: There is influence of Restrain on the decrease of violent behavior in patient of violent behavior residing in room of IGD RSJD Atma Husada Mahakam Samarinda. Keywords: Restrain, violent behavior